Overview of China high-speed railway earthquake early-warning system - Mingduan Liu; Kai Liu (High-Speed Railway, 2024)
Amidst China's aggressive expansion of its high-speed rail network, the intersection of these lines with seismic fault zones has elevated the risk profile for high-speed rail travel. To counteract the potential dangers posed by seismic disturbances, China has introduced a comprehensive high-speed railway earthquake early-warning system. This article presents an in-depth examination of this system, encompassing aspects such as its developmental evolution, architectural design, and pivotal technologies. Furthermore, it ventures into the realm of future enhancements and developmental pathways for the system, fusing emergent findings from earthquake early warning research with advancements in artificial intelligence.